Wail: The Life of Bud Powell, and The Amazing Bud Powell: Black Genius, Jazz History, and the Challenge of Bebop - Seguin, Pierre-Emmanuel (Jazz Research Journal, 2015)
Book reviews of: Peter Pullman, Wail: The Life of Bud Powell. New York: Peter Pullman, LCC, 2012. 488 pp. ISBN 978-0-9851418-1-3 (pbk). 19.99. Guthrie P. Ramsey, Jr, The Amazing Bud Powell: Black Genius, Jazz History, and the Challenge of Bebop. Berkeley: University of California Press, 2013. 240 pp. ISBN 978-0-520-24391-0 (hbk). £24.95/34.95.